Engaging with children living amidst political violence: Towards an integrated approach to protection - Jason Hart (University of Bath, Centre for Development Studies (CDS), 2014)
This paper begins with reflection upon the specific protection needs of children in settings of political violence as identified by child protection actors. It then considers the nature of institutional response offered by child-focussed humanitarian organisations. Particular attention will be paid to the challenges of public advocacy addressing the sources of harm to the young, taking into account the political agendas and sensitivities attendant to many of the world's conflict zones. From this perspective, the piece constitutes a call to consider child protection in broader political-economic context, concluding with analysis of key ways in which the field requires further development if it is to ensure not just the healing of children harmed by political violence but also more effective prevention of such harm in the first instance.
Keywords: 330; children; protection; rights; political-economy; military recruitment